2004
DOI: 10.1016/s1097-2765(04)00026-7
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomal ATPases Link Ubiquitylation of Histone H2B to Methylation of Histone H3

Abstract: In Saccharomyces cerevisiae, methylation of histone H3 at active genes is an epigenetic mark that distinguishes active from silent chromatin and functions as a short-term "memory" of recent transcription. Methylation of H3 at lysine residues K4 and K79 depends on ubiquitylation of histone H2B, but the mechanisms linking H2B ubiquitylation to H3 methylation are unknown. Here, we demonstrate that proteasomal ATPases Rpt4 and Rpt6 function to connect these two histone modifications. We show that recruitment of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
156
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(165 citation statements)
references
References 39 publications
(1 reference statement)
6
156
0
Order By: Relevance
“…Notably, H2B monoubiquitylation was subsequently found to be required for di-and trimethylation of lysine 4 and lysine 79 of histone H3 at transcribed chromatin [42][43][44][45][46][47][48]. This pathway is conserved from yeast to mammals, and is dependent on a host of additional proteins that converge at the elongating RNA Pol II [41,[49][50][51][52][53][54]. Subsequently, the mammalian orthologs of the yeast Bre1, RNF20 and RNF40, were identified [55,56].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, H2B monoubiquitylation was subsequently found to be required for di-and trimethylation of lysine 4 and lysine 79 of histone H3 at transcribed chromatin [42][43][44][45][46][47][48]. This pathway is conserved from yeast to mammals, and is dependent on a host of additional proteins that converge at the elongating RNA Pol II [41,[49][50][51][52][53][54]. Subsequently, the mammalian orthologs of the yeast Bre1, RNF20 and RNF40, were identified [55,56].…”
mentioning
confidence: 99%
“…Thus, while carrying out its regular enzymatic activity in the DDR context, it was presumably physically and functionally detached from its regular context. In the transcription context, H2B monoubiquitylation in yeast and mammals is dependent on the early steps in transcription initiation and elongation, and the corresponding E3 ligase closely interacts with many proteins that take part in this process, some of which associate directly with RNA Pol II [41,[49][50][51][52][53][54]99,100]. It is not entirely clear how many of the proteins surrounding RNF20-RNF40 in the transcription context accompany this heterodimer to the DNA damage sites.…”
mentioning
confidence: 99%
“…H2B ubiquitination is a prerequisite for a second modification on a different histone. Methylation of H3 at lysine residues depends on the ubiquitination of histone H2B (46). Reduced ubiquitination of H2B reduces H3 lysine-79 di-methylation and correlates with a decreased gene expression.…”
mentioning
confidence: 99%
“…H2B ubiquitylation is reportedly higher at active genes than at the silenced telomeres (Emre et al, 2005), and both the recruitment and activity of the H2B-ubiquitylation machinery are regulated by interactions with the transcriptional apparatus, including pol II (Xiao et al, 2005), the Paf complex (Ng et al, 2003;Wood et al, 2003b;Xiao et al, 2005), and Bur kinases (Wood et al, 2005). At active genes, H2B ubiquitylation is essential for the processive methylation of histone H3 at lysine residues K4 and K79 (Dover et al, 2002;Sun and Allis, 2002;Dehe et al, 2005;Shahbazian et al, 2005), but not K36 (Li et al, 2003;Wood et al, 2003b), and for recruitment of proteasomal ATPases to chromatin (Ezhkova and Tansey, 2004). Although only ϳ10% of steady-state H2B is monoubiquitylated (Robzyk et al, 2000), it is likely that a much larger percentage of H2B is actually ubiquitylated and that deubiquitylation is an active and crucial process (reviewed in Emre and Berger, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As described above, poly-Ub chains could recruit Ub-dependent chaperones to chromatin, which in turn facilitate the known functions of K123 ubiquitylation. Indeed, we have previously found that H2B ubiquitylation is required for recruitment of 19S proteasomal ATPases to chromatin (Ezhkova and Tansey, 2004) and that mutations in these ATPases result in loss of histone H3 (K4 and K79) methylation, which is itself a Rad6 -Bre1/ K123-dependent process. This finding has led us to propose that 19S proteins come to chromatin in a Ub-dependent manner and promote H3 methylation by altering local chromatin structure.…”
mentioning
confidence: 99%